Intelligence Analysis on the Threat of Illegal Imports in the Tanjung Balai Karimun Border Area - Sari, Puspita; Riyanta, Stanislaus; Yoesgiantoro, Donny (IHSA Institute, 2025)
This study aims to analyze the threat of illegal imports in the Tanjung Balai Karimun border area, which has a strategic location in the Malacca Strait and is vulnerable to smuggling activities. Illegal imports are a serious problem that can disrupt economic, social, and political stability, with impacts in the form of loss of state revenue, circulation of dangerous goods, and threats to privacy. The research method used is a qualitative approach with in-depth interviews, direct observation, and analysis of official documents, such as Customs data enforcement. The results of the study are expected to provide strategic recommendations to strengthen national border control policies and improve regional cooperation to maintain security and stability in the Tanjung Balai Karimun border area